PENERAPAN MODEL COOPERATIVE LEARNING TIPE INDEX CARD MATCH DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS IV SDN GLONTOR TAHUN AJARAN 2012/2013 - SUNARSIH, SUNARSIH (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Application of Model Cooperative Learning Index Card Match type in increasing student learning social studies class IV Glontor SDN Academic Year 2012/2013. This research is a classroom action research that aims to: describe the application of cooperative learning instructional model types Index Card Match, enhance social studies learning, and describe the challenges and solutions. The experiment was conducted in three cycles. The subjects were all class IV students at SDN Glontor which totaled 34. Source data comes from teachers and students. Data collection techniques used observation, interviews, tests, and documentation. The validity of the data using data triangulation technique. Data analysis with qualitative and quantitative analysis. The results show that the application of model Cooperative Learning Index Card Match types can improve learning Social Studies class IV students Glontor SDN Academic Year 20122/2013. Keywords: Index Card Match, Learning, IPS Abstrak: Penerapan Model Cooperative Learning tipe Index Card Match dalam peningkatan pembelajaran IPS siswa kelas IV SDN Glontor Tahun Ajaran 2012/2013. Penelitian ini adalah Penelitian Tindakan Kelas yang bertujuan: mendeskripsikan penerapan model Cooperative Learning tipe Index Card Match, meningkatkan pembelajaran IPS, dan mendeskripsikan kendala dan solusi. Penelitian dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah seluruh siswa kelas IV SDN Glontor yang berjumlah 34. Sumber data berasal dari guru dan siswa. Teknik pengumpulan data menggunakan observasi, wawancara, tes, dan dokumentasi. Validitas data menggunakan teknik triangulasi data. Analisis data yang digunakan dengan analisis kualitatif dan kuantitatif. Hasilnya menunjukkan bahwa penerapan model Cooperative Learning tipe Index Card Match dapat meningkatkan pembelajaran IPS siswa kelas IV SDN Glontor Tahun Ajaran 2012/2013. Kata Kunci: Index Card Match, Pembelajaran, IPS.